2020
DOI: 10.1038/s41598-020-69936-6
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale spontaneous self-organization and maturation of skeletal muscle tissues on ultra-compliant gelatin hydrogel substrates

Abstract: cellular self-organization is the fundamental driving force behind the complex architectures of native tissue. Yet, attempts at replicating native tissue architectures in vitro often involve complex microfabrication methods and materials. While impressive progress has been made within engineered models of striated muscle, the wide adaptation of these models is held back by the need for specific tools and knowhow. In this report, we show that C2C12 myoblasts spontaneously organize into highly aligned myotube ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…S2 ). While not crucial for the barrier function explored, the shape of the cell culture area can align, for instance, muscle cells 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S2 ). While not crucial for the barrier function explored, the shape of the cell culture area can align, for instance, muscle cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Cells sense the stiffness of their growth matrices 21 , 22 , and the intrinsic biodegradability of hydrogels is considered a crucial feature during tissue regeneration 23 . Various natural, synthetic, and hybrid biomaterials such as Poly (ethylene glycol) (PEG) 24 , silk 25 , Matrigel 8 , decellularized tissues 26 , and gelatin 5 , 16 , 27 29 have been explored in the literature. An advantage of hydrogels is that they are often transparent, which is not always the case for filters.…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, myotubes first elongate actively, then stabilise to a defined length, likely depending on the culture and matrix conditions ( Jensen et al, 2020 ). At this stage, myofiber ends start to establish stable connections with their environment, coinciding with their transition from immature to transitional myofibers.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that myotube culture with hydrogel covering promotes differentiation and maturation ( Maffioletti et al, 2018 ; Jensen et al, 2020 ; Urciuolo et al, 2020 ). In these reports, Matrigel diluted in the differentiation medium was used as the hydrogel material, and the myotubes indicated maturation by the expression change of various MYH gene subtypes.…”
Section: Discussionmentioning
confidence: 99%